Efektivitas Pelatihan Digitalisasi Data Posyandu Sebagai Upaya Peningkatan Monitoring Stunting Di Posyandu Tambak Lorok Kelurahan Tanjungmas Kota Semarang - Anjani, Sylvia; Agiwahyuanto, Faik; Abiyasa, Maulana Tomy; Fauziyyah , Michel Najwa (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
Gold Indonesia 2045 depends on the availability of skilled labor as evidenced by the current condition of toddlers who are physically healthy. Semarang City is one of the cities that has a high distribution of stunting cases. North Semarang is the sub-district that has the most stunted toddlers, namely with 192 toddlers, of which 84 children are in Tanjung Mas District. The aim of the research is to see the effectiveness of posyandu digitalization training as an effort to increase stunting monitoring in posyandu. This research is an experimental analytical research with a cross sectional method using a pre-post test design that compares the effect of training method interventions. The number of questions in the questionnaire is 30 items related to knowledge, attitudes and practices of digitizing posyandu data. The intervention was carried out on 19 posyandu cadres to measure the level of knowledge based on the mean difference in pre-post test results using the Wilcoxon difference test. The effectiveness of the training method using the application is measured by the Gain Score formula. The statistical results obtained a p-value of 0.001, meaning that there was a significant difference in the level of digitization of cadre data after training with a gain-score of 0.99, so it can be said that the training activities carried out had high effectiveness in increasing data digitization for cadres.